Are options on index futures profitable for risk averse investors? Empirical evidence - Jens Carsten Jackwerth; George M. Constantinides; Michal Czerwonko; Stelios Perrakis (University of Konstanz, Center of Finance and Econometrics (CoFE), 2008)
American call and put options on the S&P 500 index futures that violate the stochastic dominance bounds of Constantinides and Perrakis (2007) over 1983-2006 are identified as potentially profitable investment opportunities. Call bid prices more frequently violate their upper bound than put bid prices do, while evidence of underpriced calls and puts over this period is scant. In out-of-sample tests, the inclusion of short positions in such overpriced calls, puts, and, particularly, straddles in the market portfolio is shown to increase the expected utility of any risk averse investor and also increase the Sharpe ratio, net of transaction costs and bid-ask spreads. The results are strongly supportive of mispricing.
urn:nbn:de:bsz:352-opus-54067
Keywords: G11; G13; G14; 330; option mispricing; futures options; derivatives pricing; stochastic dominance; transaction costs; market efficiency